Health risk assessment of ciprofloxacin, tetracycline, and oxytetracycline residues in raw, frozen, and boiled broiler chicken available in a local area of Bangladesh - Haque, Shaila; Jamil, Md. Yusuf; Khan, Md. Shahinul Haque; Reza, Md. Sajib Al; Esrafil, Md.; Abedin, Md. Zainul; Zubair, Md. Abu; Sikder, Md. Asaduzzaman; Bari, Luthfunnesa (Frontiers in Antibiotics, 2024)
Introduction The misuse of antibiotics in poultry farming is a global issue. Objective The focus of this study was the health risk assessment of consumers from the determination of ciprofloxacin (CIP), tetracycline (TC), and oxytetracycline (OTC) in broiler chicken in the raw, frozen, and boiled stages using solid-phase extraction, high-performance liquid chromatography, and ultraviolet detection (SPE-HPLC-UV). Materials and methods Chromatographic separation was achieved using 0.3% metaphosphoric acid and acetonitrile (1:10, v/v) for CIP at 280 nm and oxalic acid (0.01 M) and acetonitrile (1:1, v/v) for TC and OTC at 355 nm with different retention times. The method had an acceptable precision with good linearity, specificity, limit of detection, limit of quantification, accuracy, and stability. Results Among a total of 252 raw samples, approximately 68.25%, 25.4%, and 7.54% contained CIP, TC, and OTC, respectively. Out of the positive raw samples, CIP exceeded the maximum residual limit (MRL) in 3.6% muscle, 14.3% liver and 17.9% skin samples, whereas TC and OTC were below the MRLs. The residual concentrations of these antibiotics were almost unchanged in frozen samples. After boiling the chicken samples, the TC and OTC residues were reduced significantly compared to CIP. Although the concentrations of CIP in boiled samples were above the MRL set by the European Union, these did not exceed the hazard index 1. Conclusion Based on these results, the exposure levels to antibiotics in broiler chicken meats may be considered to have a low risk for human health.